Charge recombination losses in thiophene-substituted porphyrin dye-sensitized solar cells. (March 2016) - Arrechea, Susana; Clifford, John N.; Pellejà, Laia; Aljarilla, Ana; de la Cruz, Pilar; Palomares, Emilio; Langa, Fernando
Abstract: Two new porphyrins that incorporate thiophene substituents as spacers between the conjugated porphyrin core and the anchoring cyanoacrylate group have been synthesised. The two dyes differ in the number of thiophene bridges; porphyrin1a has only one thiophene group and porphyrin1b has two thiophene rings connected by a double bond. The measured light-to-energy conversion efficiencies in1a and1b were assessed using two different electrolytes, LP1 and LP2, which differ in the presence of tert -butyl pyridine in LP1. An efficiency of 6% under standard measurement conditions has been achieved for1a + LP1. However, for porphyrin1b the use of electrolyte LP1 led to lower efficiencies and a value of approximately 4% was obtained. The differences between the two types of solar cells and the electrolytes have been studied in-depth using photo-induced time-resolved techniques such as CE (Charge Extraction) and TPV (Transient PhotoVoltage). Graphical abstract: Highlights: Two new Zn-porphyrin-thiophene- cyanoacrylic dyes have been synthesized. Efficiencies up to 6% has been achieved. IPCE, photo-induced charge recombination and electron lifetimes studies were carried out.